Characterization of human S-adenosyl-homocysteine hydrolase in vitro and identification of its potential inhibitors - Weiwei Hao; Yanhua Li; Qiuli Shan; Tian Han; Wencheng Li; Sheng He; Kongkai Zhu; Yumei Li; Xiaojun Tan; Jinsong Gu (Taylor & Francis Group, 2017)
Human S-adenosyl-homocysteine hydrolase (SAHH, E.C.3.3.1.1) has been considered to be an attractive target for the design of medicines to treat human disease, because of its important role in regulating biological methylation reactions to catalyse the reversible hydrolysis of S-adenosylhomocysteine (SAH) to adenosine (Ado) and l-homocysteine (Hcy). In this study, SAHH protein was successfully cloned and purified with optimized, Pichia pastoris (P. pastoris) expression system. The biological activity results revealed that, among the tested compounds screened by ChemMapper and SciFinder Scholar, 4-(3-hydroxyprop-1-en-1-yl)-2-methoxyphenol (coniferyl alcohol, CAS: 458-35-5, ZINC: 12359045) exhibited the highest inhibition against rSAHH (IC50= 34 nM). Molecular docking studies showed that coniferyl alcohol was well docked into the active cavity of SAHH. And several H-bonds formed between them, which stabilized coniferyl alcohol in the active site of rSAHH with a proper conformation.